Visual Field Test With Gaze Check Tasks: Application in a Homonymous Hemianopic Patient Unaware of the Visual Defects - Shibuki, Katsuei; Yokota, Tsuyoshi; Hirasawa, Akane; Tamura, Daisuke; Hasegawa, Shin; Nakajima, Takashi (Frontiers in Neurology, 2021)
Gaze control is required for applying visual stimuli to a particular area of the visual field. We developed a visual field test with gaze check tasks to investigate hemianopia. In this test, participants must report the presence or absence of visual stimuli when a small object at the fixation point vibrates. Trials in the absence of visual stimuli were used as gaze check tasks, since the vibration could be observed only when the gaze was directed at the fixation point. We evaluated the efficacy of our test in four control participants and one patient with homonymous hemianopia who was unaware of the defects in the left visual field. This patient presented hemianopia in the test with gaze check tasks, but not when the gaze check tasks were omitted. The patient showed spontaneous gaze movements from the fixation point to the upper left direction, as well as scanning of the left visual field during the test without gaze check tasks. Thus, we concluded that the visual defects in this patient were compensated in daily life by spontaneous eye movements coordinated with visual information processing. The present results show the usefulness of the visual field test with gaze check tasks.